Assessment of postgraduate students attitudes and competencies in the use of ICT: A case of nigerian students at the Universiti Sultan Zainal Abidin, Malaysia - Rahimah, Embong; Mustafa, Mamat; Fadzli, Adam; Ado, Abdu Bichi (2016)
ICT is an important tool in education and research. ICT is the leading centaury's revolution for the enhancement of teaching, learning, research, personal and professional development at all level of education . The focus of 21stcentury postgraduate studies is basically on research and the role of ICT in research has been highlighted in various studies. This study investigates the attitudes and competency of postgraduate students in the use of ICT resources. Also field of studies on their attitude and competence were examined. 77 postgraduate students from the graduate school were randomly selected for the study. 41 items questionnaire was designed and administered to the respondents. The means, percentages and t-test statistics were to analyse the data. Results showed that majority of the postgraduate students' attitude is positive and they are competent in the use of some simple ICT resources. Similarly, there was no significant difference between sciences based and non-sciences based postgraduate students' attitudes. However, there was a significant difference between sciences based and non-sciences based competence in the use of ICT resources. This study provides evidence that; the postgraduate students may lack the necessary competence in to fully integrate of ICT in research. It is recommended that, a special training program on ICT should be introduced by the university with needed hands-on experiences in order to promote ICT integration into postgraduate research. Further study should be conducted with different variables and focus on assessing whether ICT competence affect ICT attitude.